ANTHROPOLOGICAL AND FOLK ASPECTS OF THE CREATION OF THE MAGNETISER CHARACTER IN THE WORKS OF ERNST THEODOR AMADEUS HOFFMAN AND JOZEF DZIERZKOWSKI - Dylewska, Agnieszka (Literatura Ludowa. Journal of Folklore and Popular Culture, 2018)
The fascination with magnetism, both on the scientific and literary levels, was a phenomenon always inextricably connected to Romanticism. Magnetism and the mysterious figure of the magnetiser were a subject of interest for many Romantic writers, including E.T.A. Hoffman and Jozef Dzierzkowski. Both writers made the magnetic doctor their main protagonist. The discourse about magnetic cures became a constitutive issue in their musings. This article offere an analysis of the portraits of the magnetisers in Magnetiseur (1814) by E.T.A. Hoffmann and in The Magnetic Doctor (1844) by Józef Dierzakowski. Its goal is not only to present the title characters in relation to the assumptions of the Romantic anthropology developing at the beginning of the 19th century, but also to show that the elements derived from folklore, which was used by both writers in the creation of the image of the magnetiser, have a crucial influence on the birth of the (urban) legend connected to this figure.